Sickle cell trait: not as benign as once thought - Uqba Khan; Lauren Kleess; Justin Yeh; Charles Berko; Sapna Kuehl (Greater Baltimore Medical Center, 2014)
We describe a case of renal papillary necrosis in a middle-aged female with sickle cell trait who presented with gross hematuria. We wish to highlight this case for several reasons. Sickle cell trait is often viewed as a benign condition despite the fact that it is associated with significant morbidity such as renal papillary necrosis and renal medullary carcinoma. Appropriate evaluation needs to be undertaken to promptly diagnose renal papillary necrosis and differentiate it from renal medullary carcinoma as this can result in deadly consequences for patients. CT urography has emerged as a diagnostic study to evaluate hematuria in such patients. We review the pathophysiology, diagnosis, and management of renal papillary necrosis in patients with sickle cell trait.